PENGARUH PENGANGGARAN PARTISIPATIF TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN - Wulandari, Diana Eka; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test empirically the influence of participatory budgeting to the managerial performance on the Local Government Work Unit of Surabaya city. This research also meant to test empirically whether the organization commitment and leadership style which is moderated by the participatory budgeting to the managerial performance in the Local Government Work Unit of Surabaya city. This research which applies survey method has been done by issuing questionnaires. The sample collection technique has been done by using purposive sampling. The analysis technique has been done by performing simple regression analysis to test the influence of participatory budgeting to the managerial performance. Meanwhile, the test of organization commitment and the leadership style as the moderated variable has been done by using Moderated Regression Analysis (MRA). The result of this research shows that: first, the participatory budgeting has positive influence to the managerial performance. Second, organizational commitment is unable to moderate the influence of participatory budgeting to the managerial performance. Third, leadership style is moderated by the influence of participatory budgeting to the managerial performance.Keywords: Participatory Budgeting, Managerial Performance, Organization Commitment, Leadership Style.